Male superiority and famale resistance in Indonesian fairytales themed Seven Nymphs - Ryan Hidayat; Fauzi Rahman; Denik Wirawati; Muhammad Sega Sufia Purnama (BAHASTRA, 2021)
Story of Seven Nymphs spread in Indonesia implies many similarities starting from the introduction of stories, conflicts, the peak of conflict, and settlement. Story of seven nymphs always describes them as helpless before men when their shawls stolen. The aim of this study is to show how male superiority and resistance of women represented in folklore stories themed seven nymphs. The method used in this study is the content analysis method with comparative literature and sociological literature technique. The data taken from story titled Jaka Tarub, Telaga Bidadari, Arya Menak, Raja Omas, and Mahligai Keloyang. The story have similar lines, but comes from different regions. The results of the research and analysis show that the superiority of men has begun to seen from the actions in the story that took the nymph’s shawl (wings). With that event, the nymphs figure told in all research data described as having no power to fight, so that without other choices, they must be willing to be the wife of a man who stole their shawl. However, in women (nymphs), there is the potential for strength and endurance in facing their new life in the world. All men who intend to marry nymphs in the story made helpless and obey all kinds of conditions and restrictions proposed by the nymphs if they want to marry them. Finally, in the analysis, the overall story ends in the separation between the man and his wife (the nymphs) because the agreement at the beginning violated by the male character.